Kompetensi Pedagogik Guru Pendidikan Agama Katolik dalam Gerakan Literasi Sekolah Dasar di Sekolah Dasar Negeri 004 Datah Bilang Ulu - Bano, Julita; Lorensius Lorensius; Donatus Dole (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The pedagogical competence of Catholic religious education teachers in implementing the School Literacy Movement (SLM) is crucial for enhancing students' literacy skills, which contribute to character development. This study aims to describe the implementation of the pedagogical competence of Catholic religious education teachers in the school literacy movement at SD Negeri 004 Datah Bilang Ulu. This qualitative study employed interviews, observations, and documentation to collect data from 10 informants, consisting of Catholic religious education teachers, homeroom teachers, the principal, and students. The collected data were analyzed using interactive analysis, starting from data collection, reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the pedagogical competence of Catholic STRATEGI PEMASARAN YANG DILAKUKAN DI PLAZA TUNJUNGAN III SURABAYA DALAM MEMASARKAN SEMUA PRODUKNYA 2 Lumen - VOLUME 1, NO. 1, JUNI 2022 religious education teachers in SLM includes: (1) literacy guidance outside of school, (2) extending literacy learning to the home, (3) introducing basic literacy, and (4) using creative teaching methods. This shows that Catholic religious education teachers are capable of understanding students' learning characteristics, using diverse and adaptive teaching methods, and communicating effectively to facilitate efficient learning in supporting students' literacy skills. However, based on the evaluation results, the SLM program at this school is still in its initial implementation phase or habituation phase. This indicates that the school is not yet fully prepared to implement SLM comprehensively, primarily due to a lack of resources, the roles of teachers, the principal, and community participation that have not been maximized, as well as the need for increased government support. This means that while the school is committed, it has not yet implemented it according to the established guidelines and has not reached the stage of providing innovations and becoming a driver for advancing SLM.